Performance of logistics intelligent storage scene in 5G private network - Shilei DONG; Jingbo ZHAO; Peng HUANG (Dianxin kexue)
Intelligent warehousing introduces intelligent operation terminals in the logistics warehousing link to realize the automation of the assembly line to execute various warehousing business and it needs to rely on high-quality network services to realize tasks such as real-time data perception, allocation, and job control.In different warehousing operation processes and operation areas, there are differentiated intelligent terminals, operation scenarios and communication requirements.The actual warehousing scenarios was combined to achieve 5G private network coverage for smart warehousing, network quality assurance under the deep integration mechanism of 5G private network and warehousing industry was explored, and a customized regional network deployment plan was proposed, which plays a role as a benchmark model for the full implementation of the 5G private network-based intelligent storage system.